Popular Culture as an Educative Teaching Tool in the Elementary Classroom - Romeo, Raquel; Ryan, Thomas (Universitas Tanjungpura, 2023)
The purpose of this research was to investigate popular culture as a means to educate in the elementary school classroom. Using secondary research in education and cultural studies, we investigated how teachers can use popular media to enhance student learning and develop critical media literacy skills. Findings revealed popular culture is a helpful teaching tool in elementary school classrooms. Knowledge of popular culture does not impede education but is a large part of students